How Technological Self-Efficacy Influences Academic Engagement: The Mediating Role of Learning Motivation Among Vocational Students - Asrianti Clara Agnestiara; Fransisca Irina Roesmala Dewi; Sri Triatri (Green Publisher Indonesia, 2025)
The development of technology in the digital era requires the readiness of Vocational High School students, especially in the field of technology and information systems, to optimize the use of technology in the learning process. This challenge is related to students’ academic engagement, which is influenced by technology self-efficacy and learning motivation. This study aims to analyze the relationship between technology self-efficacy and academic engagement, as well as to examine the mediating role of learning motivation in this relationship. This study employs a non-experimental quantitative approach with a correlational design involving students majoring in Network and Application Information Systems, Computer and Network Engineering, and Software Engineering at SMK X Jakarta. The instruments used include the School Engagement Measure, the Computer User Self-Efficacy Scale, and the Academic Motivation Scale. Data collection was conducted online, and data analysis was carried out using SEM through JASP and SmartPLS software. The results of the analysis show that technology self-efficacy has a significant effect on academic engagement, both directly and indirectly through learning motivation as a partial mediator. These findings confirm that technology self-efficacy and learning motivation are key factors in enhancing the academic engagement of vocational school students. The practical implications of this research encourage schools and educators to design digital-based training and intervention programs aimed at improving technology self-efficacy and learning motivation, so that the academic engagement of vocational school students can be optimized in facing the challenges of the digital-era workforce.